Sediment resuspension enhances nutrient exchange in intertidal mudflats - Rios-Yunes, Dunia; Grandjean, Tim; di Primio, Alena; Tiano, Justin; Bouma, Tjeerd J.; van Oevelen, Dick; Soetaert, Karline (Frontiers in Marine Science, 2023)
Intertidal coastal sediments are important centers for nutrient transformation, regeneration, and storage. Sediment resuspension, due to wave action or tidal currents, can induce nutrient release to the water column and fuel primary production. Storms and extreme weather events are expected to increase due to climate change in coastal areas, but little is known about their effect on nutrient release from coastal sediments. We have conducted in-situ sediment resuspension experiments, in which erosion was simulated by a stepwise increase in current velocities, while measuring nutrient uptake or release in field flumes positioned on intertidal areas of a tidal bay (Eastern Scheldt) and an estuary (Western Scheldt). In both systems, the water column concentration of ammonium (NH4+) and nitrite (NO2-) increased predictably with greater erosion as estimated from pore water dilution and erosion depth. In contrast, the phosphate (PO43-) dynamics were different between systems, and those of nitrate (NO3-) were small and variable. Notably, sediment resuspension caused a decrease in the overlying water PO43- concentration in the tidal bay, while an increase was observed in the estuarine sediments. Our observations showed that the concentration of PO43- in the water column was more intensely affected by resuspension than that of NH4+ and NO2-. The present study highlights the differential effect of sediment resuspension on nutrient exchange in two contrasting tidal coastal environments.